Optimalisasi Pencegahan Balita Stunting Melalui Penyuluhan Dan Pelatihan Pada Kader Di Desa HangTuah, Kec. Perhentian Raja, Kab. Kampar - Suyanto, Suyanto; Afandi, Dedi; Wahyuni, Sri; Zulharman, Zulharman; Restila, Ridha; Dzakwan, M. Alif; Anggraini, Shella; Azzahra, Puan Justitia; Eriyan, Muhammad Firdaus; Darmawan, Daniel; Maysa, Hana; BDM, Nurfifi Pratiwi; Fitra, Julia; Fimadani, Ersa; Putri, Rintan Dwi (Riau Journal of Empowerment, 2024)
Stunting is a chronic nutritional disorder that causes children's height growth to be inappropriate for their age. This linear growth disorder is caused by a chronic lack of nutritional intake, especially during the First 1000 Days of Life (HPK) which starts from the time of conception until the child is 2 years old and/or due to repeated chronic infections. The factor of poor nutritional intake during pregnancy is related to the baby's low birth weight so that the baby can experience malnutrition from the womb until birth. The aim of the activity is to optimize the prevention of stunting in toddlers through counseling and training for cadres in Desa Hangtuah, Kec. Perhentian Raja, Kab. Kampar. The methods used are discussion, compression and simulation starting from the preparation stage, creating educational media such as posters and banners, counseling and simulating the use of anthropometric kits. The results obtained from activities can increase participants' knowledge and skills. It is hoped that with this activity participants can pass on the information obtained to other Hangtuah Village communities so that they can prevent stunting as early as possible.